Sediment load analysis in Lake Chini - Norlida, Mohd Dom; Sharina, Sulaiman; Norashikin, Ahmad Kamal; Saerahany Legori, Ibrahim; Nadiatul Adilah, Ahmad Abdul Ghani; Junaidah, Ariffin (Department of Irrigation and Drainage, Ministry of Natural Resources and Environment Malaysia, 2016)
This study is significant to be conducted to reduce the physical impacts of human activities such as water quality deterioration and destabilization of the stream bed and banks. The mining activity near Jemberau River can destabilize channel form, which may result in sedimentation at the downstream area. The rate of sediment discharge and the rate of water quality deterioration are expected to increase near the mining area close to Jemberau River. Bedload and suspended load sampling were carried out in the dry and wet months from September to December 2016. High suspended solid concentrations (SSC) were recorded in Chini and Jemberau Rivers especially during the wet months. Total Maximum Daily Load (TMDL) estimation for 5, 10, 15 and 20 years are also given.